PENGATURAN TANGGUNG JAWAB SOSIAL DAN LINGKUNGAN BADAN USAHA MILIK NEGARA PADA PERSEROAN TERBATAS PELABUHAN INDONESIA (PERSERO): Regulation Of Social And Environmental Responsibility Of State-Owned Enterprises At Pelabuhan Indonesia (Persero) - Aime Qothrunnada Fabian; Sri Bakti Yunari (Faculty of Law, Universitas Trisakti, 2025)
The social and environmental responsibilities in the context of state-owned enterprises (BUMN) are regulated by laws that emphasize the importance of sustainability and contributions to community welfare as well as environmental protection. Pelindo as BUMN has an obligation to implement social and environmental responsibility consistently and measurably. The research method used in this study is normative-juridical with descriptive approach, aimed at describing and analyzing the regulation of social and environmental responsibility at Pelindo. This study examines the regulation of Social and Environmental Responsibility (TJSL) at Pelindo in relation to internal policies and prevailing laws, the types of TJSL programs implemented, and how their social and environmental impacts are evaluated. The result and conclusion: internal supervision is conducted by company management through periodic assessments, while external oversight involves relevant ministries and the public to ensure compliance and community benefit. The TJSL program of Pelindo reflects the company's commitment to creating a positive social impact through the improvement of education quality and the economic empowerment of the community. Through the implementation of structured, directed, and measurable TJSL programs, Pelindo can play a key role in realizing inclusive, sustainable, and environmentally friendly development.